PEMBELAJARAN DIFERENSIASI SEBAGAI PILAR IMPLEMENTASI KURIKULUM MERDEKA - Rosfiani, Okta; Saidah, Rafika Kauna; Itsnaini, Muhammad Fahmi; Rifaldi, Rafly Purnama; Firliansyah, Farhan (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2025)
This qualitative study aims to examine the function of differentiated learning as the basis for implementing The autonomous curriculum in relation to accommodating the diversity of student needs. This research is motivated by the urgency of implementing The Self-Sustained Curriculum which emphasizes flexibility and independence in learning, where differentiation is a key strategy to realize the principle of "teaching according to student abilities". Data was gathered using classroom observations, document analysis and in-depth interviews with principals and instructors (RPP, teaching modules, diagnostic assessments) at Madrasah As Sa'adah, PAI teachers and 4 students. Utilizing the Miles-Huberman method for data analysis interactive model with thematic coding. The research findings reveal: 1) differentiated learning is the main pillar in realizing the essence of the Independent Curriculum through adjusting learning environments, procedures, goods, and content according to student profiles; 2) differentiation increases active participation and intrinsic motivation of students with interest-based tasks and personal scaffolding; supporting factors include ongoing teacher training and collaboration of teaching teams, while the main challenges are administrative burdens and gaps in pedagogical understanding. The conclusion states that differentiated learning is not just an additional strategy, but the core of the operationalization of the Independent Curriculum to achieve holistic educational goals. The study recommends strengthening teachers' capacity in differentiation design and simplifying their support systems. ABSTRAKPenelitian kualitatif ini bertujuan untuk mengkaji peran pembelajaran diferensiasi sebagai landasan implementasi Kurikulum Merdeka dalam konteks mengakomodasi keberagaman kebutuhan siswa. Kajian ini dilatarbelakangi oleh urgensi implementasi Kurikulum Merdeka yang menitikberatkan pada fleksibilitas dan kemandirian belajar, di mana diferensiasi menjadi strategi kunci untuk mewujudkan prinsip “mengajar sesuai kemampuan siswa”. Data dikumpulkan melalui observasi kelas dan wawancara menyeluruh dengan guru dan kepala sekolah. serta analisis dokumen (RPP, modul ajar, asesmen diagnostik) di Madrasah As Sa'adah, Guru PAI dan Siswa 4 orang. Model interaktif yang diciptakan oleh Miles-Huberman digunakan untuk melakukan analisis data dengan koding tematik. Temuan penelitian mengungkap: 1) pembelajaran diferensiasi menjadi pilar utama dalam mewujudkan hakikat Kurikulum Merdeka melalui modifikasi konten, prosedur, produk, dan lingkungan belajar berdasarkan profil siswa; 2) diferensiasi meningkatkan partisipasi aktif dan motivasi alami siswa untuk tugas berbasis minat dan perancah pribadi; faktor pendukung meliputi pelatihan guru yang berkelanjutan dan kolaborasi tim pengajar, sedangkan tantangan utamanya adalah beban administratif dan kesenjangan pemahaman pedagogis. Kesimpulannya menyatakan bahwa pembelajaran diferensiasi bukan hanya strategi tambahan, tetapi inti dari operasionalisasi Kurikulum Merdeka untuk mencapai tujuan pendidikan holistik. Penelitian merekomendasikan penguatan kapasitas guru dalam desain diferensiasi dan penyederhanaan sistem pendukung mereka.